Effect of Range Of Motion (ROM) Training in Patients with Physical Mobility Disorders to Increase Muscle Strength in Cibeureum Wetan Village, Sumedang Regency - Sahra Nabilah; Mutiara Mutiara Annallisa bella; Meynur Rohmah; Bambang Eko Supriyanto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Mobility or mobilization is a person's ability to move and carry out activities easily, freely and regularly to meet their daily needs, either independently, with the help of others, or only with the help of tools. The factors that affect mobility are starting a lifestyle if the lifestyle is not healthy such as from food, lack of exercise and lack of free movement can affect a person's mobility, age and developmental status if a person's age is increasing and developmental status such as decreased muscle strength can affect mobility in contrast to a young age who has strong energy in moving (Asyifa, 2023). Therefore, the goals we give to the elderly with physical mobility disorders are in the form of an appropriate and effective way to carry out Range Of Motion (ROM) Training, This community service aims to describe the application of ROM exercises in patients with physical mobility disorders. The form of this scientific paper is in the form of a case study on 4 patients who experience physical mobility disorders. The research instrument was in the form of a family knowledge sheet about ROM exercises. This case study was conducted for 4 days with a frequency of 1 time a day with ROM training intervention. The results of the case study showed that the problem of physical mobility disorders experienced by 4 respondents, there were 2 respondents who experienced an increase and 2 respondents who did not experience an increase in muscle strength after doing ROM exercises. The conclusion of therapy (ROM) may increase muscle strength in some respondents. Advice for families is expected to always provide assistance during implementation so that it can be a support system for respondents so that they can help respondents in doing ROM exercises at home.